Implementasi E-SDM Di PT. Asia Pacific Fibers Tbk. Karawang - Yugi Primacipta; Uus Mohammad Darul Fadli (CV. ITTC INDONESIA, 2024)
Technology has played a very significant role in changing the way organizations operate and has drastically affected human resource management (HRM) practices, further increasing its influence. The implementation of technology in HR management practices can improve organizational efficiency and effectiveness. The implementation of technology in HR management can include things such as: (a) electronic organizational structure, business processes, and document tracking; (b) electronic workforce planning; (c) electronic recruitment systems; (d) personal information systems, salary accounts, leave, and electronic exit procedures; (e) electronic job evaluation and electronic remuneration systems; (f) electronic performance management systems; (g) electronic training and development; (h) career management and electronic talent management. PT Asia Pacific Fibers, located in Kiara Payung Village, Klari District, Karawang, West Java, aimed to understand the implementation process of E-SDM in their HR activities. This research uses a qualitative research design with a case study approach and involves interviews with 5 respondents as well as data collection methods through observation, in-depth interviews, and documentation to support information related to the implementation of E-SDM in HR activities.